Salinity is a prevailing factor for amelioration of wheat blast by biocontrol agents - Cabot, Catalina (2018)
Plants exposed to combined abiotic and biotic stress conditions may show enhanced pathogen resistance. Biocontrol agents (BCAs) can further contribute to ameliorate plant responses to these complex situations. In recent years, wheat production has been challenged by the expansion of salt-affected soils as well as by severe outbreaks of emerging diseases such as wheat blast. Here, the role of two BCAs, Pseudomonas stutzeri AN10 and Trichoderma harzianum Th56, was examined in salt-stressed seedlings infected with two Pyricularia oryzae isolates of contrasting aggressiveness. BCAs did not enhance plant tolerance to high salt stress. However, BCAs improved performance of salt-stressed wheat plants infected with the less aggressive Pyricularia isolate. The lower infection in salt-stressed BCAs-treated plants could be due to a salt-induced priming state required to trigger an early expression of plant defence genes.